Elastic properties of the sigma W-Re phase: A first principles investigation. (February 2017) - Bonny, G.; Bakaev, A.; Terentyev, D.; Mastrikov, Yu.A.
Abstract: We perform density functional theory (DFT) calculations to obtain the formation enthalpy and six independent elastic constants for the 32 possible occupations of the five non-equivalent sites of the σ -phase. The obtained results suggest linear correlation between bulk modulus and Re concentration and between shear modulus and formation enthalpy. The results are used to parameterize a sublattice model with ideal mixing on each sublattice for the free energy and elastic constants. The model allows one to predict the equilibrium composition on each sublattice and hence elastic constants as a function of global Re concentration and temperature of the W-Re alloy. Graphical abstract: